2007
DOI: 10.1021/bm7008813
|View full text |Cite
|
Sign up to set email alerts
|

Collagen–DNA Complex

Abstract: Previously presented models of collagen-DNA (7) and collagen-siRNA (8) complexes point to a general description of delivery systems and indicate to what specific topology that system should be equipped with to effectively deliver the gene into the living body via in vivo and in vitro injection. We focused our interest on the nature of collagen-DNA complex structure and the molecular and environmental determinants of the self-association processes of collagen with the presence of DNA. In this aspect, the self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…In addition, hydroxyapatite binds and inactivates nucleases (5). The interaction of DNA with collagen and its role in long-term preservation of DNA in ancient tissue is less well understood, but it has been hypothesized that DNA-collagen complexes, which form spontaneously in aqueous solutions in vitro, might play a protective role (3, 6). …”
mentioning
confidence: 99%
“…In addition, hydroxyapatite binds and inactivates nucleases (5). The interaction of DNA with collagen and its role in long-term preservation of DNA in ancient tissue is less well understood, but it has been hypothesized that DNA-collagen complexes, which form spontaneously in aqueous solutions in vitro, might play a protective role (3, 6). …”
mentioning
confidence: 99%
“…For example, in aqueous solution the double helices of DNA form tightly packed complexes with up to 15 triple helices of collagen (Mrevlishvili and Svintradze, 2005;Svintradze et al, 2008). It is known that the DNA establishes strong bonds with the surrounding molecules.…”
mentioning
confidence: 99%
“…The Rpn values for native collagen at different temperatures show minor differences from that of the collagen-DNA conjugate at different concentrations. The collagen-DNA conjugate formation was initiated due to the electrostatic interaction as well as hydrogen bonding between the donor group like CH 2 , CH (OH) of type I collagen and the acceptor phosphate group of DNA [6,29,32]. The hydrogen bonding are created directly either by collagen(CH)· · ·DNA(PO 4 ), or by collagen(CH)· · ·H 2 O· · ·DNA(PO 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…If a system in which a gene vector is embedded in inactive biomaterial is administered into the living body, then the gene vector and bioactive protein can be protected from immunological and enzymatic attack. Thus, the release of the gene vector from the biomaterial and the gene expression period can be controlled [6][7][8]. Hence, it was found that DNA double helix and collagen triple helix will create a supramolecular self-assembly system in aqueous solution that will cause the rise in stability of DNA against the nucleases as well as the collagen developing the autoimmune reaction [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation